IDENTIFIKASI Salmonella Sp. DAN Escherichia coli PADA LALAT DI TEMPAT PENJUALAN DAGING PASAR NAIKOTEN KOTA KUPANG - Theresia Setia Palus; Maxs U.E. Sanam; Annytha I.R. Detha (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2016)
The flesh is a source of protein from animal which have high nutrition value but are perishable. Salmonella sp. and Escherichia coli are pathogenic bacteria in flesh that can cause food-borne disease. The contamination of bacteria is cause by the lack of personal hygiene and sanitation so the flesh damaged easily by flies as the vector such as Musca domestica and Chrysomya megacephala. This study aims to determine the value of Total Plate Count (TPC) and whether the flies body surface are contaminated by Salmonella sp. and Escherichia coli. A total of 122 sample flies taken from butcheries. The result showed that all of samples were contaminated by the Salmonella sp. and Escherichia coli. The value of TPC showed that the average of level contamination from the highest to the lowest, started from 1,8 x 107 CFU/g, followed 7,5 x 106 CFU/g and 9,19 x 105CFU/g. In conclusion, flies take from meat sales have the high value of TPC and contaminated by Salmonella sp..and Escherichia coli.